The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/jgs.15734
|View full text |Cite
|
Sign up to set email alerts
|

Health Service Use Among Chinese American Older Adults: Is There a Somatization Effect?

Abstract: BACKGROUND/OBJECTIVES: Somatization of depressive symptoms among Chinese American older adults remains understudied. This study aimed to identify whether the relationship between depressive symptoms and use of health services (ie, doctor visits, hospital, and emergency department) could be due to pain and whether acculturation played a role in the relations among depressive symptoms, pain, and health service use. DESIGN AND PARTICIPANTS: Secondary data came from the Population Study of Chinese Elderly in Chica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
(32 reference statements)
1
8
0
Order By: Relevance
“…In addition, health service use was also associated with depression in this study, indicating that depression may predict health service use to some extent. In a study on American older adults, depressive symptoms were positively related to health service use [42], which is consistent with our results. A possible reason for this association is that depressive symptoms lead older people to have a negative perception of their health, thereby increasing their use of health services.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, health service use was also associated with depression in this study, indicating that depression may predict health service use to some extent. In a study on American older adults, depressive symptoms were positively related to health service use [42], which is consistent with our results. A possible reason for this association is that depressive symptoms lead older people to have a negative perception of their health, thereby increasing their use of health services.…”
Section: Discussionsupporting
confidence: 92%
“…These findings suggest that acculturation among elderly immigrants may not be a strong variant predicting health outcomes because they tend to have low level of acculturation in general. Nevertheless, assessing cultural effects on health may be important to better understand the Asian elderly immigrants’ health and healthcare use [ 19 ] because low acculturation level may suggest a lower likelihood of adjusting to the new culture.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have reported an association between acculturation and chronic pain, the results are somewhat sparse by age group; a relatively high level of acculturation was found among young immigrants [ 17 , 18 ], and more acculturated immigrants had a higher prevalence of chronic pain [ 18 ]. Among elderly immigrants, a relatively low level of acculturation was reported [ 19 ], and acculturation did not directly correlate with somatization [ 20 ], which is often associated with pain complaints.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding social relationships, three articles concentrate on various facets of the social contexts of Chinese families including filial piety from the perspectives of the older adult and their adult children and older adults' capability for social engagement . Lastly, two articles explore patterns of health behaviors among Chinese older adults to understand potential predictors and consequences of certain health behaviors …”
mentioning
confidence: 99%